Informative water supply challenges on the development of towns: a study of Minna town central Nigeria / Salihu Ibrahim and Ahmad Zaharuddin Sani Ahmad Sabri - Ibrahim, Salihu; Ahmad Sabri, Ahmad Zaharuddin Sani (Universiti Teknologi MARA, Kedah, 2018)
'Water is life' so a common saying of ages. The purpose of this paper is to examine the challenge faced by developing nations about scarcity of portable water supply in view of the ever increasing population and development of towns. Scholars have documented works on infrastructural deficiency in the third world towns and cities and have mostly looked at the problem with levity as government sees provision of safe water as privilege. This paper aims at establishing the effects of poor quality water supply on our lives and the consequent impact on the development of towns. The scope of the study is Minna Municipality which has been experiencing rapid growth since it became a state capital and the movement of Nigeria's federal capital city from Lagos to Abuja. The researcher utilizes both primary and secondary data. The research findings indicates that people prefer and converge more on where there is available and clean water and poor quality water supply brings about diseases.